2022
DOI: 10.3389/fendo.2022.927834
|View full text |Cite
|
Sign up to set email alerts
|

Thinning or Opening: A Randomized Sibling-Embryo Pilot Trial on the Efficacy of Two Laser-Assisted Hatching Modes During the Extended Culture of Highly Fragmented Cleavage Embryos

Abstract: A randomized sibling-embryo pilot trial investigated whether two ways of laser-assisted hatching result in different blastulation and clinical outcomes after extended in vitro culture process of highly fragmented day-3 cleavage embryos. From 92 couples, a total of 315 highly fragmented day-3 embryos (the fragmentation >25%) were recruited and randomized into laser-assisted zona thinning (LAT, n=157) and opening (LAO, n=158) groups, and then underwent a blastocyst culture in vitro. The main endpoint meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…A research group in 2022 compared the T-LAH to D-LAH and they concluded that there is no privilege to any of them on the other regarding chemical and clinical pregnancy. This was in agreement with our research when we compared the thinning and drilling group with all age groups but we found that thinning has an advantage over the control group above the age of 35 years old while Drilling did not show any significance [27]. Also, in agreement with our study Mostafa et.al study proved that both chemical and clinical pregnancy rate improved significantly after a quarter LAH for embryos of poor prognosis women in ICSI cycles (P= 0.024).…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 93%
“…A research group in 2022 compared the T-LAH to D-LAH and they concluded that there is no privilege to any of them on the other regarding chemical and clinical pregnancy. This was in agreement with our research when we compared the thinning and drilling group with all age groups but we found that thinning has an advantage over the control group above the age of 35 years old while Drilling did not show any significance [27]. Also, in agreement with our study Mostafa et.al study proved that both chemical and clinical pregnancy rate improved significantly after a quarter LAH for embryos of poor prognosis women in ICSI cycles (P= 0.024).…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 93%
“…1 depicted the complete filtering procedure. Nine studies totaling 4 RCT [ 16 , 28 30 ] and 5 non-RCT [ 12 , 23 , 24 , 26 , 27 ] were included. The particular information traits that were examined are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After applying exclusion criteria using EndNote, 209 studies met the requirements for quantitative analysis. These studies were selected based on the reviewers' evaluation of the titles, abstracts, and full texts of the remaining 205 studies [ 12 , 16 , 23 , 24 , 26 30 ]. The literature search specifically focused on English papers, as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic approach employs proteolytic enzymes such as pronase, proteinase K, or trypsin, which selectively destroy certain proteins of the zona pellucida and result in gradual thinning [ 27 , 28 ]. However, acidic solutions such as hydrochloric or triode acids produce a chemical reaction that weakens the structure of the zona, making hatching easier [ 29 , 30 ]. Each technique attempts to achieve a selective opening in the zona pellucida, thus enhancing implantation potential for the embryo.…”
Section: Reviewmentioning
confidence: 99%